An Analysis of English Teachers’ Perception of Merdeka Curriculum at Elementary Schools in Lubuklinggau - Checilia Fristiviona; Maria Ramasari; Sastika Seli (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research aims to determine the perceptions of Elementary Schools English teachers towards the implementation of Merdeka Curriculum. This research used a qualitative descriptive method. The data is collected by using questionnaires. This research involved 9 English teachers in Lubuklinggau Timur I of Elementary Schools. The results showed that English teachers have a positive perceptions of Merdeka Curriculum. In conclusion, Merdeka Curriculum has many positive impacts on students, teachers, and the teaching and learning process. The positive impact on students is that students became more active, independent, and improvement based on student interests. In addition, a positive impact on teachers are given self-independent in the teaching and learning process. The teachers are free to express ideas about how to teach and keep the classroom atmosphere more comfortable.